Rectifying structure with high voltage operation based on CuBO2 as an UV photocatalyst - Soylu, M.; Al-Ghamdi, Ahmed A.; Bin Omran, Saad; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2014)
CuBO2/p-Si diode is a new rectifying structure with photosensing, which is a candidate for producing high voltage protection circuit in electronic application. It has been seen that the photocurrent in the reverse bias I-V characteristic is strongly increased by photo-illumination. It is believed that the combination of thin CuBO2 layer and p-Si will provide high voltage protection level, which does not exist for conventional Si diodes. The capacitance and conductance-voltage characteristics were measured at various frequencies. The results indicate that the electrical parameters of CuBO2/p-Si diode are affected by the series resistance and interface states. The optical properties of the CuBO2 thin film were analyzed by UV-vis-NIR spectrophotometry and FTIR studies. The optical band gap of the CuBO2 is lOcated in the ultraviolet (UV) range. In this spectral range, the B-O-B bonds and relationship between Cu2+-O are confirmed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Heterojunctions; Sol-gel synthesis; X-ray diffraction; Light absorption and reflection